Penerapan Model Project Based Learning (PjBL) Untuk Meningkatkan Hasil Belajar Siswa Materi Bijak Menggunakan Uang Di Kelas II SD Inpres Sempan Barat Timika - Rina Anggraini (BADAN PENERBIT STIEPARI PRESS, 2022)
This study originated from problems in learning Indonesian language in class II SD Inpres Sempan Barat Timika where most students have difficulty in understanding Indonesian language learning materials, so that the learning outcomes obtained by students are low. Therefore, to improve student learning outcomes in Indonesian language learning on wise money use materials, the Project Based Learning Model was applied to grade II students of SD Inpres Sempan Barat Timika. This research is a classroom action research (PTK) using a qualitative approach. This research was conducted on grade II students of SD Inpres Sempan Barat Timika with a total of 24 students. The instruments used to collect data were observation sheets, documentation and learning outcome tests. The data obtained in the study were analyzed using qualitative and quantitative data analysis. This research was conducted in two times cycle and each cycle consists of one meeting. The results of research from each cycle that has been carried out using the Project Based Learning Model show an improvement in both the learning process and student learning outcomes. This can be seen from the achievement of students in learning, where in cycle I the average score obtained by students only reached 70.8% completeness with an average student score of 68.75, while in cycle II showed a fairly high increase with completeness reaching 87.5% and an average student score of 82. Thus it can be concluded that the use of Project Based Learning Model can improve student learning outcomes in learning Indonesian Language in class II SD Inpres Sempan Barat Timika.